Biomass Production and Ester Synthesis by In Situ Transesterification/Esterification Using the Microalga Spirulina platensis - Tatiana Rodrigues da Silva Baumgartner; Jorge Augusto Mendes Burak; Dirceu Baumgartner; Gisella Maria Zanin; Pedro Augusto Arroyo (International Journal of Chemical Engineering)
The increasing energy demand and reduction in the availability of nonrenewable energy sources, allied with an increase in public environmental awareness, have stimulated a search for alternative energy sources. The present study was aimed at producing biomass from the microalga Spirulina platensis and at assessing in situ synthesis of alkyl esters via acid transesterification/esterification of biomass to produce biodiesel. Two alcohols (ethanol and methanol) and two cosolvents (hexane and chloroform) were tested, at different temperatures (30, 45, 60, 75, and 90°C) and reaction times (10, 20, 30, 60, and 120 min). The factorial analysis of variance detected an interaction between the factors (): temperature, reaction time, alcohol, and cosolvent. The best yields were obtained with the combination ethanol and chloroform at 60°C, after 30 min of reaction, and with hexane at 45°C, after 10 min of reaction. In situ transesterification/esterification of alga biomass to form esters for biodiesel production adds unconventional dynamics to the use of this feedstock.